Development of hyoimmunogenic pasta and its immunochemical validation with celiac disease patients' sera. Issue 1 (June 2015) - Susanna, S.; Prabhasankar, P.
Abstract: The present study was carried out with an aim to develop low immunogenic pasta by altering the pH of Triticum durum flour and immunological validation of pasta using patients' sera. Modification of T. durum wheat flour was carried out by altering pH of the flour using lactic acid, sodium bicarbonate and natural ingredients such as tomato, spinach puree. The pH altered flours were taken for rheological studies and also extruded into pasta using lab scale extruder. Pasta quality characteristics were analyzed and Celiac disease patients' sera was used for immunological validation of pasta. Immunoreactivity of alkaline modified pasta with IgA anti-gliadin antibodies of patients' sera was markedly reduced than control and acid modified pasta as indicated by both Dot-Blot and ELISA. Quality evaluation showed the acceptable and comparable product quality parameters. The study indicated that altering the pH of wheat flour chemically to pH 9.00 is effective in reducing immunogenic property of wheat flour and comparable quality pasta thus developed pasta could be beneficial for patients with celiac disease. However modification occurring at epitope structure of gliadin due to alkaline condition and safety on long term consumption of this product needs to be evaluated further. Highlights: Modification of wheat flour by altering pH to reduce gliadin immunogenic property. Modified flours based pasta were evaluated immunochemically with CD patient's sera. Immunoreactivity of alkaline modified pasta was reduced than control pasta. Alkaline modified wheat flour able to produce comparable good quality pasta. Developed pasta may be beneficial for CD patients.